Political Foundations of Racial Violence in the Post-Reconstruction South - Testa, Patrick A; Williams, Jhacova (Quarterly Journal of Economics, 2026)
Abstract Election results act as powerful signals, shaping social behavior in ways that can be dramatic and even violent. This article shows how racial violence in the post-Reconstruction U.S. South was tied to the local performance of the anti-Black Democratic Party in presidential elections. Using a regression discontinuity design based on close presidential vote shares, we find that Southern counties where Democrats lost the popular vote between 1880 and 1900 were nearly twice as likely to experience Black lynchings in the following four years. Despite no corresponding changes in local office holding, these defeats were salient among local elites. We show that Southern newspapers, closely aligned with the Democratic Party, amplified narratives of Black criminality in the aftermath of Democratic losses. Such accusations were, in turn, frequently invoked by lynch mobs. These findings point to the strategic use of racial violence by Democratic elites, foreshadowing the institutionalized vote suppression of Jim Crow.